Identifying the key organisational human factors for introducing human-robot collaboration in industry: an exploratory study. Issue 9 (December 2015) - Charalambous, George; Fletcher, Sarah; Webb, Philip
Abstract The concept of industrial human-robot collaboration (HRC) is becoming increasing integrated into production lines as a means for enhancing productivity and product quality. Previous literature suggests that the implementation of any technological change should not merely be seen as an engineering challenge. Inattention to the human element has been highlighted a major barrier impeding organisations from grasping the full benefits of the technological change being introduced. With the concept of industrial HRC still at its infancy, it is crucial to understand which organisational human factors are of most importance. To our knowledge, a framework with the key organisational human factors that need to be considered by organisations for the successful implementation of industrial HRC does not exist. To this end, the aim of this work is to develop a human factors framework of the key organisational human factors that influence the success of industrial HRC implementation. A theoretical framework was developed which collected the key organisational human factors by reviewing comparable contexts to HRC. Following this, to identify whether the organisational human factors outlined in the theoretical framework were enablers or barriers, an industrial exploratory case study was conducted where traditional manual work was being automated. The implications from this exploratory case study make the first attempt to provide organisations with a roadmap of the key organisational human factors that need to be considered for the implementation of industrial HRC Furthermore, the inter-relations between the organisational human factors are highlighted as well as further work.